Sanchari - Khopkar, Arun.; Samson, Leela ([India Ministry of External Affairs ], 1991)
A documentary on Bharatanatyam dance, a dance form from Tamil Nadu in Southern India.
VHS.
Script, direction and production, Arun Khopkar.
Keywords: Bharata natyam; Dance -- India; Educational videos